Deficiência auditiva: estudos clínicos sobre o narcisismo materno - Asano, Cassia Yuri; Neme, Carmen Maria Bueno [UNESP]; Yamada, Midori Otake (My University, 2010)
The diagnosis of hearing loss (HL) in a child constitutes a crisis, includinga possible crash in parental narcissism, requiring an individual, matrimonial andfamiliar reorganization process. The mother is the main figure to devote herselfattending the baby and generally takes the most responsibilities in the processof habilitation or rehabilitation of the child, while still having to deal with her frustratedexpectations and narcissism. This study aims to investigate the effects of a deaf child’s birth on the mother’s narcissism. Here understood as a normal stage of psychosexual development of the human being, needed for life preservation, nota pathology. Five different clinical pratical studies were developed with mothers of deaf children that were diagnosed less than one year ago. The data were collected using individual semi-structured interviews and Thematic Apperception Test (TAT). Based on these studies it was found that the birth of a deaf child makes it difficult to obtain the expected narcissist satisfaction. The mother, investing all her affection and longing almost only on her child, hopes to rebuild her dream obtaining the "cure" and "normality" of her baby by submitting him/her to a cochlear implant.

O diagnóstico de deficiência auditiva (DA) em um filho constitui-se uma situação de crise que inclui uma possível quebra no narcisismo parental, demandando um processo de reorganização individual, conjugal e familiar. A mãe é a principal figura a dedicar-se aos cuidados com o bebê e é ela quem geralmente assume maiores responsabilidades no processo de habilitação ou reabilitação da criança, tendo ainda que lidar com suas expectativas e narcisismo frustrados. Este estudo visa investigar os efeitos do nascimento de um filho com DA no narcisismo materno, aqui entendido como estágio normal da evolução psicossexual do ser humano, necessário para a preservação da vida, e não como patologia. São realizados cinco estudos clínicos de mães de crianças com DA, diagnosticadas estas últimas há menos de um ano. Os dados são coletados por meio de entrevistas individuais semiestruturadas e do Teste de Apercepção Temática (TAT). Constata-se que o nascimento de um filho com DA dificulta a satisfação narcísica esperada e que investindo seus afetos e anseios quase que unicamente na criança, a mãe espera reconstruir seu sonho, obtendo a "cura" da deficiência e a "normalidade" do filho, por meio do implante coclear.
Hearing impairment: clinical studies about maternal narcissism
Keywords: Maternal narcissism; Hearing impairment; Psychoanalysis; Narcisismo materno; Deficiência auditiva; Psicanálise